Problematika Hak Anak Luar Kawin: Tinjauan Kitab Undang-Undang Hukum Perdata - Muhammad Habibi Miftakhul Marwa (Universitas Muhammadiyah Yogyakarta, 2023)
The position of children in the family is very important, because their presence in the world brings happiness to parents. However, not all children fare well. Children born outside of marriage have a double burden in society. They occupy the lowest strata and are even stigmatized as illegitimate children. This article aims to determine the regulation of the position of extra-marital children and the legal consequences of the recognition of extra-marital children according to the Civil Code and the fiqh of children's rights. This research is a type of normative legal research because it uses secondary data obtained from literature studies. The data is analyzed descriptively with a conceptual approach and statute approach. The results of this study indicate that the provisions of extra-marital children are regulated in the Civil Code Chapter XII concerning Fatherhood and the Origin of Children. Extra-marital children only get biological and juridical civil rights after being legalized by the authorities or recognized by their parents. The existence of this recognition has legal consequences in the form of a civil rights relationship between parents and unmarried children to jointly carry out their rights and obligations.